Reveal Voluntary Auditor Switching Determinants in Indonesia: Evidence from Financial Services Sector - Wibowo, Puji; Rahmawati, Ai (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
Many argue that factors affecting voluntary auditor switching by clients have not been commonly agreed. This research attempts to investigate whether management change, company growth, the credibility of auditor, and audit tenure both simultenously and partially influence voluntary auditor switching by auditee. We use public companies from financial services listed in Indonesian Capital Market over period 2011-2016 as research objects. We conduct logistic regression to reveal whether relationship between those variables exists. Based on our analysis, we conclude that those four independent variables have no significant impacts on voluntary auditor rotation. This result not only confirms some previous studies but also contrary with a number of former researches. Therefore, we suggest that future research shall take other variables into account such as good corporate governance components to obtain more convincing results